2001
DOI: 10.1002/j.2161-1882.2001.tb00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Change Reports by Clients in a University Counseling Center: Relationship to Inquiry Technique, Client, and Situational Variables

Abstract: This study examined the effect of inquiry technique at intake on reports of pretreatment change.There was no statistically significant difference in the percentage of clients who reported pretreatment change regardless of which format was used. The study also examined 5 client and situational variables and obtained no significant differences.hange is the essence of counseling. Regardless of the specific probem or complaint, clients enter counseling to alter themselves and their C circumstances. Investigation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In contrast, few studies have focused on change that occurs prior to entering treatment. In the general psychotherapy literature, studies of pretreatment change have shown that symptom change consistently occurs after the initial phone call when an appointment is scheduled, before the first treatment session (Kindsvatter et al, ; Lawson, ; Ness and Murphy, ; Weiner‐Davis et al, ; West et al, ). In the substance abuse literature, a similar pattern has been observed in studies that report reductions in or cessation of use that occurs between the initial phone call and the first clinical research assessment (Epstein et al, ; Kaminer et al, ; Morgenstern et al, ; Ondersma et al, ; Penberthy et al, ; Sobell, ; Stasiewicz et al, ).…”
mentioning
confidence: 99%
“…In contrast, few studies have focused on change that occurs prior to entering treatment. In the general psychotherapy literature, studies of pretreatment change have shown that symptom change consistently occurs after the initial phone call when an appointment is scheduled, before the first treatment session (Kindsvatter et al, ; Lawson, ; Ness and Murphy, ; Weiner‐Davis et al, ; West et al, ). In the substance abuse literature, a similar pattern has been observed in studies that report reductions in or cessation of use that occurs between the initial phone call and the first clinical research assessment (Epstein et al, ; Kaminer et al, ; Morgenstern et al, ; Ondersma et al, ; Penberthy et al, ; Sobell, ; Stasiewicz et al, ).…”
mentioning
confidence: 99%
“…In the general psychotherapy literature, studies of pretreatment change have consistently shown significant decreases in symptoms after the initial phone call—when an appointment is scheduled—and before the first treatment session (e.g., Kindsvatter, Osborn, Bubenzer, & Duba, 2010; Lawson, 1994; Ness & Murphy, 2001; Weiner-Davis, de Shazer, & Gingerich, 1987; West, Harvey-Berino, Krukowski, & Skelly, 2011). Similar patterns of change in drinking behaviors have also been reported for those entering treatment for alcohol use disorders.…”
mentioning
confidence: 99%
“…Subsequently, systematic attempts to elicit this information by means of a series of 'pre-therapy change' questions have identified problem improvement in 25% to 50% or more of new clients (Johnson, Nelson, & Allgood, 1998;Lawson, 1994;Ness & Murphy, 2001;Throckmorton, Best, & Alison, 2001). Interestingly, some of these clients did not even recognise that such improvement had occurred until being prompted to think about it (Lawson, 1994).…”
Section: Part 1: the Process Of Seeking Counsellingmentioning
confidence: 98%